Everyday Life and Social Contacts of Dementia and Non-Dementia Residents over 80 Years in Long-Term Inpatient Care: A Multi-Level Analysis on the Effect of Staffing - Melanie Zirves (MDPI AG, 2021)
The relationship between nurse staffing, physical outcomes of residents, as well as quality of care receives major attention. The impact of staffing levels on residents’ ability to organize their everyday life and maintain social contacts, however, has not been analyzed to date. This study examines whether a relationship between the staff-to-resident ratio for registered nurses and nursing home residents with and without dementia aged over 80 exists. Secondary data collected in the project inQS (indikatorengestützte Qualitätsförderung) were used (n = 1782, mean age = 88.14). The analyzed cross-sectional data were collected in winter 2019 in facilities of the Diocesan Caritas Association in Germany. A sum score formed from variables measuring residents’ abilities to independently organize their everyday life and maintain social contacts functioned as the dependent variable. A multi-level regression analysis was performed. The results revealed that the ability of residents without dementia was significantly associated with the staff-to-resident ratio of registered nurses. This was not true for residents with dementia. For the latter, however, whether the facility offers a segregated care unit turned out to be significant. Additional and longitudinal research is indispensable to explain the inequality between the two groups analyzed.